Comparison of the efficacy of two anticonvulsants, phenytoin and valproate to improve PCP and d-amphetamine induced deficits in a reversal learning task in the rat - Idris, Nagi F.; Neill, JO C.; Large, Charles H. (Frontiers in Behavioral Neuroscience, 2009)
Recent studies in our laboratory have shown that PCP (phencyclidine) and d-amphetamine induce a cognitive deficit in rats, in a paradigm of potential relevance for the pathology of schizophrenia. Atypical, but not classical antipsychotics and the anticonvulsant, lamotrigine have been shown to prevent a selective reversal learning deficit induced by PCP. In contrast, only haloperidol reversed the d-amphetamine-induced deficit. The present study aimed to explore the ability of two anticonvulsants with differing mechanism of action, valproate and phenytoin to attenuate the cognitive deficits induced by PCP and d-amphetamine in the reversal learning paradigm. PCP at 1.5mg/kg and d-amphetamine at 0.5mg/kg both produced a selective and significant reduction in performance of the reversal phase with no effect on the initial phase of the task in female-hooded Lister rats. Valproate (25-200mg/kg) and phenytoin (25-50mg/kg) had no effect on performance when administered alone. Valproate (100-200mg/kg), whose principle action is thought to be the enhancement of GABA transmission, was unable to prevent the cognitive deficit induced by either PCP or d-amphetamine. Conversely, phenytoin (50mg/kg), a use-dependent sodium channel inhibitor, significantly prevented the deficit induced by PCP, but not d-amphetamine. These results add to our earlier work with lamotrigine, and suggest that sodium channel blockade may be a mechanism by which some anticonvulsant drugs can prevent the PCP-induced deficit. These data have implications for the use of anticonvulsant drugs in the treatment of cognitive or psychotic disorders.